Avaliação e caracterização dos sedimentos transportados no Rio Vacacaí Mirim - Rizzardi, Alencar Simão (2013)
The processes of erosion and sedimentation in a watershed cause numerous problems. Knowledge of the amount of sediment transported by rivers is really important to planning and using water resources, since the damage caused by sediments depend on the amount and nature of them, which depend on the processes of erosion, transport and deposition. This study aimed to evaluate the sediment transport in the Vacacaí-Mirim River, through measured data in the cross-section in Restinga Sêca. Thus, it was possible to quantify the average of the sediment discharge in cross-section of the river; to characterize the particle size of the transported materials; to relate the sediment discharge (Qs) and liquid discharge (Q) to the hydraulic and geometric characteristics of the section; and to indicate the sediment discharge calculation method most suitable to estimate sediment transport. To calibrate the quality of collected data, it was used the Pearson correlation coefficient (r), and the index of dispersion (ID) presented by Aguirre et al. (2004), which is the average of the deviations between the calculated and measured values in the field. When it was related the Qs and Q to the hydraulic and geometric parameters of the section, it was found that Q had very strong correlation (r> 0.90) with the wet area, cross-sectional width, wetted perimeter, hydraulic radius and the stage of the section. The best fit to the Qs were using the stream stage and average depth of the flow.The sediment discharge of the river was almost all wash load. The wash load particle size distribution was 57.05% of silt, 39.81% of coarse clay and 3.14% fine sand. The greater coefficient of variation was found to diameter D90 (64.31% to bed material and 73.21% to drag material. Related to particle size analysis of the bed material, it was found a predominance of sand (97.21%) and silt (2.79%), which does not differ significantly from the drag material, 97.06% sand and 2.94 % silt. After determining the rating curve of sediments, it was possible to estimate the total average of sediments discharge for the considered period, which resulted in more than 182 tons of sediment per year for the considered section. Related to procedures used to evaluate the sediment discharge, Einstein modified method was which best fit the QST measure (ID = 0.07), followed by Colby (1957), Toffaleti (1969) with ID equal to 2.04 and 3.53, respectively. To estimate the bed load discharge, the best method was Meyer-Peter & Müller (1948), resulting in a ID equal to 7.02 followed by methods of Karim (1998), Van Rijn (1984) and Cheng (2002). The methods of Modified Einstein and Colby (1957), which incorporate measured data of suspended sediment concentration (SSC), resulted in better evaluations related to sediment discharge calculated and measured. Thus, it is recommended to measure SSC and subsequently applying these two methods to determine the sediment discharge in the Vacacaí-Mirim River.